The Polar Exploring Expedition. A special meeting of the American Geographical & statistical society, held March 22, 1860. - American Geographical Society of New York. (New York, Printed for the Society, 1860)
Treats of the proposed expedition to the Arctic regions by Dr. I.I. Hayes. Mode of access: Internet.